The Role of Self-Esteem, Family Relationships, and Social Support With Mental Health Among High School Adolescents: A Cross-Sectional Study - Arianti, Diana; Sari, Yuli Permata; Sanusi, Ihsan; Ulva, Fadillah; Ifayanti, Titin (Chakra Brahmanda Lentera Institute, 2026)
Background: Adolescent mental health has become a major public health concern worldwide. Although self-esteem, family relationships, and social support are recognized as important psychosocial protective factors, evidence regarding their combined contribution to adolescent mental health in the Indonesian context remains limited. This study aimed to examine the associations of self-esteem, family relationships, and social support with mental health among high school adolescents. Methods: This cross-sectional study was conducted among 146 high school students aged 15–18 years in Padang, West Sumatra, Indonesia, and reported in accordance with the STROBE guidelines. Participants were selected using simple random sampling. Self-esteem, family relationships, social support, and mental health were assessed using the Rosenberg Self-Esteem Scale (RSES), Family Adaptability and Cohesion Evaluation Scale IV (FACES-IV), Multidimensional Scale of Perceived Social Support (MSPSS), and General Health Questionnaire-12 (GHQ-12). Data were analyzed using descriptive statistics, chi-square tests, and multivariable ordinal logistic regression, with adjusted odds ratios (AORs) and 95% confidence intervals (95% CIs) reported to identify factors associated with adolescent mental health. Results: Bivariate analysis indicated that gender, self-esteem, family dynamics, and social support were significantly correlated with adolescent mental health (all p < 0.05). In the multivariable ordinal logistic regression model, adolescents with low self-esteem had significantly lower odds of being in a higher mental health category compared to those with high self-esteem (AOR = 0.00004; 95% CI: 0.000001–0.002; p < 0.001). Similarly, adolescents with weak family ties had reduced chances of improved mental health compared to those with strong family ties (AOR = 0.0002; 95% CI: 0.000005–0.007; p < 0.001). Gender continued to show a significant association with adolescent mental health (AOR = 82.43; 95% CI: 3.63–1877.76; p = 0.006), while social support lost its significance after adjustment. Conclusion: Self-esteem, family relationships, and social support were significantly associated with adolescent mental health. Although they were not independent predictors in the multivariate model, these factors remain important psychosocial resources. Mental health promotion programs should target multiple psychosocial domains simultaneously, particularly within school and family environments.